Effect of prebiotic content on functional and physicochemical properties of Lactobacillus casei loaded chitosan-Ca-alginate microparticles - Tanja Petreska Ivanovska; Kristina Mladenovska; Zoran Kavrakovski; Liljana Bogdanovska; Anita Grozdanov; Emil Popovski; Lidija Petrushevska-Tozi (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
This study aims to evaluate the influence of different concentrations of fructooligosaccharide (FOS) as prebiotic on functional and physicochemical properties of Lactobacillus casei loaded chitosan-Ca-alginate microparticles prepared by spray-drying method, after preparation and 6-month storage at 4 °C. Prebiotic compound positively influenced the viability of L. casei during preparation of the microparticles and in storage conditions, while no significant difference of the probiotic viability was observed when different concentrations of FOS in a range of 1.5 - 5% w/w were applied. Having in regard that non-significant improvement in the functional and physicochemical properties of the microparticles with increased content of the FOS was observed, the concentration of 1.5% w/w was recommended as an optimal for preparation of synbiotic loaded microparticles.